Hemodynamic study in 3D printed stenotic coronary artery models: experimental validation and transient simulation. Issue 6 (26th April 2021) - Carvalho, Violeta; Rodrigues, Nelson; Ribeiro, Ricardo; Costa, Pedro F.; Teixeira, José C. F.; Lima, Rui A.; Teixeira, Senhorinha F. C. F.
Abstract: Atherosclerosis is a progressive disease that can significantly reduce blood supply to vital organs, being one of the main causes of death worldwide. In this work, a numerical and experimental study in 3D printed stenotic coronary arteries, considering both steady and pulsatile blood flow conditions, is presented. The results revealed that a degree of stenosis superior to 50% creates disturbed flows downstream of the contraction, with an accented increase in the wall shear stress measurements at the stenosis throat. Finally, the multiphase mixture was investigated and compared with a single-phase modelling, and only slight differences were observed right after the stenosis throat.